AN EMPIRICAL STUDY OF THE DRIVERS OF CONSUMER ACCEPTANCE OF MOBILE ADVERTISING (SHORT MESSAGE SERVICES) IN INDONESIA - Anabelle Paramita Ratihayu; Lita Agustina; M. Farhan Baihaqi; Andreas Raharso4 (Bina Nusantara University, 2008)
Today, mobile marketing has been used for ‘a new media’ to advertise any marketing campaign for the company. In Indonesia, we can find a lot of mobile marketing campaign via mobile device and usually mentioned as SMS advertising. Many researchers have proven how good the effect of mobile advertising, the acceptance, and also consumers’ attitude of the impact of SMS advertising. In this paper we explore and do the research about the consumers’ acceptance toward advertising via mobile device. In addition, for the research we use several variables that were: consumers’ utility, consumers’ utilization of contextual information, consumers’ control, consumers’ sacrifice, consumers’ trust, and the last is frequency of exposure about the mobile advertising itself. This research is done using questionnaire to find out the Indonesian customer acceptance toward mobile advertising via mobile device. The result of this research tells that customer utilities, contextual, control, sacrifice, and trust of the SMS advertising are significantly affecting the acceptance about receiving mobile advertising; The frequency of exposure from SMS advertising are not significantly affect the customer acceptance toward mobile advertising via mobile device. With this result mobile advertising via message can deliver effectively and meet the company objective. Thus based on this research our prejudice about consumer acceptance in Indonesia mostly proven that consumers’ perceived utility, perceived contextual, perceived control, trust, perceived sacrifice are have significant correlation within the customer acceptance but for frequency of exposure did not have enough evidence to accepted and did not have significant correlation between consumers’ acceptance.